Urgent Therapeutic Grafting of Platelet-Rich Fibrin Membrane in Descemetocele. Issue 9 (September 2016) - Can, Mehmet Erol; Dereli Can, Gamze; Cagil, Nurullah; Cakmak, Hasan Basri; Sungu, Nuran
Abstract : Purpose: To report the clinical and histopathological results of a novel autologous scaffold grafting, platelet-rich fibrin (PRF) membrane, in cases with descemetocele. Methods: Three patients with severe corneal stromal melting and central descemetocele caused by neurotrophic keratopathy and infective keratitis underwent PRF membrane grafting on the central cornea for the prevention of imminent corneal perforation. After a quiescent 3-month period, penetrating keratoplasty and cataract extraction were performed for visual rehabilitation in 1 patient and host corneal tissue was examined histopathologically. Results: Pain was significantly relieved, conjunctival inflammation was markedly resolved, and the central descemetocele area became thicker with scar formation in all patients. Histopathological examination revealed fibrosis formation over the descemetocele area without any tissue gap. Newly formed tissue containing irregular corneal lamellae covered the fibrosis formation and accounted for the prevention of perforation. Conclusions: Temporary PRF membrane grafting may be an alternative intervention to avoid impending corneal perforation in cases with severe descemetocele. Abstract : Supplemental Digital Content is Available in the Text.